ANALYSIS OF THE IMPACT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) STRATEGIES ON PRODUCT AVAILABILITY AND BUSINESS SUSTAINABILITY OF MYCOLA FARMA'S PHARMACY BUSINESS - Ridzal Wahid; Christina Whidya Utami (Jurnal Bisnis dan Keuangan, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG)-based strategic planning on product availability and business sustainability at Mycola Pharmacy. Using a qualitative approach through in- depth interviews, observations, and document analysis involving the pharmacy owner, pharmaceutical wholesalers, employees, and consumers, the research highlights how ESG implementation strengthens supply chain efficiency , optimizes stock management, and promotes transparent governance. The social and governance dimensions of ESG further enhance customer loyalty , operational effectiveness, and corporate reputation, contributing to long-term business sustainability amid external challenges such as the pandemic and inflation.